Case Report: Effective Treatment for Acute Chlorpyrifos Poisoning Complicated by a Non-ST-Segment Elevation Myocardial Infarction - Ye, Changqing; Zhang, Qiang; Chao, Yongsheng; Yin, Chun (Frontiers in Cardiovascular Medicine, 2021)
Background: Acute myocardial infarction (AMI) is a rare complication of acute organophosphorus pesticide poisoning. Though chlorpyrifos has been widely used as organophosphate insecticide, few cases of AMI complicated by chlorpyrifos poisoning have been reported. Suitable treatment strategy remains to be explored. Case presentation: Based on clinical manifestation, medical history, results of auxiliary examination and serum biomarkers, a 65-year-old male farmer with nausea, vomiting, chest tightness and pain was clearly diagnosed as severe chlorpyrifos self-poisoning with acute non-ST-segment elevation myocardial infarction. Because the patient and his families confirmedly refused coronary intervention, conservative treatment was applied instead. To be noted, there were some conflicts of management in chlorpyrifos poisoning and AMI. Rapid atropinisation not only contributed to the relief of muscarinic symptoms, but increased heart rate and myocardial oxygen consumption of patients with AMI. In addition, reduction of platelet aggregation, which was necessary for coronary recanalization of AMI patients, would aggravate gastrointestinal injury caused by poisoning. In this case, these conflicts were properly addressed, which led to excellent effect and prognosis of patient. Conclusions: The case of acute chlorpyrifos poisoning with AMI was reported for the first time. It was emphasized that patients with chest pain or coronary heart disease should be treated with atropine more cautiously because of the possible AMI. Moreover, proper resolution of conflicts in management for chlorpyrifos poisoning and AMI played contributing roles in improvement.